A cell-free organelle-based in vitro system for studying the peroxisomal protein import machinery - Rodrigues, TA (2016)
Here we describe a protocol to dissect the peroxisomal matrix protein import pathway using a cell-free in vitro system. The system relies on a postnuclear supernatant (PNS), which is prepared from rat/mouse liver, to act as a source of peroxisomes and cytosolic components. A typical in vitro assay comprises the following steps: (i) incubation of the PNS with an in vitro-synthesized 35 S-labeled reporter protein; (ii) treatment of the organelle suspension with a protease that degrades reporter proteins that have not associated with peroxisomes; and (iii) SDS-PAGE/autoradiography analysis. To study transport of proteins into peroxisomes, it is possible to use organelle-resident proteins that contain a peroxisomal targeting signal (PTS) as reporters in the assay. In addition, a receptor (PEX5L/S or PEX5L.PEX7) can be used to report the dynamics of shuttling proteins that mediate the import process. Thus, different but complementary perspectives on the mechanism of this pathway can be obtained. We also describe strategies to fortify the system with recombinant proteins to increase import yields and block specific parts of the machinery at a number of steps. The system recapitulates all the steps of the pathway, including mono-ubiquitination of PEX5L/S at the peroxisome membrane and its ATP-dependent export back into the cytosol by PEX1/PEX6. An in vitro import(/export) experiment can be completed in 24 h.